Dynamical mechanical behaviors of rubber-filled wood fiber composites with urea formaldehyde resin - Feiyu Tian; Xinwu Xu (Journal of Bioresources and Bioproducts, 2022)
Wood composites glued with thermosetting synthetic resins tend to show inadequate damping performance caused by the cured resinous matrix. Waste rubber maintains prominent elasticity and is feasible to be an optional modifier. To that end, composite panels of granulated tire rubber (GTR) powders and thermal-mechanically pulped wood fibers were fabricated in this study. Urea formaldehyde (UF) resin was applied as the bonding agent (10% based on wood/rubber total weight). Dynamical mechanical analysis (DMA) was conducted to disclose the thermo-mechanical behaviors of the rubber-filled wood fiber composites. Influence of two technical parameters, i.e., GTR powder size (0.55–1.09 mm) and addition content (10%, 20% and 30% based on wood/rubber total weight), was specifically discussed. The results showed that storage modulus (E') of the rubber-filled composite decreased while loss factor (tan δ) increased monotonously along with elevated temperature. A steady “plateau” region among 110–170 °C was found where both E' and tan δ keep constant. Accordingly, tan δ showed two peak values at 103–108 and 231–233 °C due to glass transition of lignin and thermal degradation of hemicellulose, respectively. Addition of rubber fillers resulted in lower bending and internal bonding strengths as well as storage modulus values. When the temperature was above 183 °C, all the rubber-filled composites showed higher tan δ values than the control. The findings above fully demonstrate the improved damping performance of the UF-bonded wood fiber composites on account of rubber component. Further work is still needed to optimize the rubber/fiber interfacial bonding strength.